Impact of serpentinized peridotite mine waste on the composition and quality of sediments in the Ría de Ortigueira (Galicia, NW Spain). (February 2021) - Guevara, P.; Pérez-Alberti, A.; Carballo, R.; Sánchez, M.; López, I.; Otero, X.L.
Abstract: The Ría de Ortigueira is an environmentally well conserved; however, the sediments show high concentrations of toxic elements. In some zones, the concentrations of Ni (60–1080 mg kg −1 ) and Cr (9–567 mg kg −1 ) were extremely high, while the concentrations of other toxic elements were within normal ranges. PCA revealed that metal enrichment was due to dumping of waste sludge from a peridotite mine. The study of marine currents showed that the exit of the contaminated waste towards the external zone is restricted by the low energy of the residual currents, and the sludge therefore remains trapped in the internal zones. The potential ecological risk was moderate for all areas of the ría, reaching high values close to the mouth of the river Landoi. Finally, geochemical fractioning showed that most of the metals are associated with Fe oxyhydroxides which can become unstable and release adsorbed or coprecipitated metals, especially Ni. Highlights: Sediments showed high concentrations of toxic elements. The concentrations of Ni and Cr were extremely high. Metal enrichment was due to dumping of sludge from a peridotite mine. The potential ecological risk was moderate.